The political ecology of geoengineering - Bravo, Elizabeth (2013)
Several technologies have been developed to mitigate the effects of climate change in recent years, including geoengineering. This is a set of techniques that aim to reduce the amount of sunlight entering the planet, trap atmospheric CO2indeep geological strata or increase the volume of marine phytoplankton to increase sinks, at global scale. Here the conflicts that can arise around these technologies and international governance that has emerged around geoengineering are analysed.